A fast alignment method for grating-based X-ray phase-contrast imaging systems - Schuster, Max; Ludwig, Veronika; Akstaller, Bernhard; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Neumayer, P.; Funk, Stefan; Anton, Gisela (Journal of Instrumentation, 2019)
The alignment of a grating-based X-ray phase-contrast interferometer is an iterative process that requires numerous steps of changing the distances and angles between the gratings. For each alignment step an image is acquired to evaluate the detected intensity signature in order to optimize the observed moir'e pattern. Thus, a large number of images has to be taken for the alignment procedure. This is not feasible within reasonable time at X-ray sources like X-ray backlighters where the time between two X-ray shots is on the scale of hours. Here, we report on the development of a stable and transportable setup ready-to-use for grating-based X-ray phase-contrast imaging. A comprehensive set of reference images taken at a continuous beam serves as a look-up table which enables the grating alignment within very few alignment steps. Since this method features a fast, reliable and predictable alignment, it is also beneficial for grating-based X-ray phase-contrast imaging systems at common X-ray sources.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

A phase-sampling method for an X-ray Talbot-Lau scanner with continuous grating movement - Ludwig, Veronika; Akstaller, Bernhard; Schuster, Max; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Anton, Gisela (Journal of Instrumentation, 2020)
A Talbot-Lau scanner enables fast grating-based X-ray phase-contrast and dark-field imaging of large samples. We present a fast and robust scanning method based on continuous phase-sampling during the usual scan process. For that purpose the source grating is moved back and forth during the whole image acquisition procedure. The scanning method needs no specific detuning of the interferometer. The acquired images are compared to the results of a standard phase-stepping procedure. We show that high quality images are obtained by this continuous phase-sampling scanning method. One main advantage of the method is its independence of the occurring moir'e pattern shape, thus enabling an optimal alignment of the interferometer. Furthermore, the method works with a priori unknown phase-step positions. To our knowledge, this is the first time a grating is moved continuously back and forth while also the sample is in linear motion during a continuous image acquisition in Talbot-Lau imaging.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Data acquisition concepts; Inspection with x-rays; X-ray radiography and digital radiography (DR)

Design of a Talbot phase-contrast microscopy imaging system with a digital detector for laser-driven X-ray backlighter sources - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Erik; Ludwig, Veronika; Martynenko, Artem S.; Meyer, Pascal; Mozzanica, Aldo; Müller, Maximilian; Neumayer, Paul; Schuster, Max; et al. (Journal of Instrumentation, 2024)
Laser-driven shock waves in matter propagate with multiple kilometers per second and therefore require sources like a laser-driven backlighter, which emit the X-rays within picoseconds, to be able to capture sharp images. The small spatial extent of shocks in low-density materials pose challenges on the imaging setup. In this work, we present a design process for a single-shot X-ray phase-contrast imaging system geared towards these objects, consisting of a two-grating Talbot interferometer and a digital X-ray detector. This imaging system is optimized with respect to the detectable refraction angle of the X-rays induced by an object, which implies a high phase sensitivity. Therefore, an optimization parameter is defined that considers experimental constraints such as the limited number of photons, the required magnification, the size and spectrum of the X-ray source, and the visibility of the moiré fringes. In this way, a large parameter space is sampled and a suitable imaging system is chosen. During a campaign at the PHELIX high-power laser facility a static test sample was imaged which is used to benchmark the optimization process and the imaging system under real conditions. The results show good agreement with the predicted performance, which demonstrates the reliability of the presented design process. Likewise, the process can be adapted to other types of laser experiments or X-ray sources and is not limited to the application presented here.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Inspection with x-rays; Models and simulations; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Evaluation of the Weighted Mean X-ray Energy for an Imaging System Via Propagation-Based Phase-Contrast Imaging - Seifert, Maria; Weule, Mareike; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Michel, Thilo; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Anton, Gisela; Funk, Stefan; et al. (Journal of Imaging, 2020)
For imaging events of extremely short duration, like shock waves or explosions, it is necessary to be able to image the object with a single-shot exposure. A suitable setup is given by a laser-induced X-ray source such as the one that can be found at GSI (Helmholtzzentrum fur Schwerionenforschung GmbH) in Darmstadt (Society for Heavy Ion Research), Germany. There, it is possible to direct a pulse from the high-energy laser Petawatt High Energy Laser for Heavy Ion eXperiments (PHELIX) on a tungsten wire to generate a picosecond polychromatic X-ray pulse, called backlighter. For grating-based single-shot phase-contrast imaging of shock waves or exploding wires, it is important to know the weighted mean energy of the X-ray spectrum for choosing a suitable setup. In propagation-based phase-contrast imaging the knowledge of the weighted mean energy is necessary to be able to reconstruct quantitative phase images of unknown objects. Hence, we developed a method to evaluate the weighted mean energy of the X-ray backlighter spectrum using propagation-based phase-contrast images. In a first step wave-field simulations are performed to verify the results. Furthermore, our evaluation is cross-checked with monochromatic synchrotron measurements with known energy at Diamond Light Source (DLS, Didcot, UK) for proof of concepts.
CRIS-Team WoS Importer:2020-08-28

Maximum likelihood reconstruction for grating-based X-ray microscopy - Wolf, Andreas; Schuster, Max; Ludwig, Veronika; Anton, Gisela; Funk, Stefan (Optics Express, 2020)
The combination of grating-based phase-contrast imaging with X-ray microscopy can result in a complicated image formation. Generally, transverse shifts of the interference fringes are nonlinearly dependent on phase differences of the measured wave front. We present an iterative reconstruction scheme based on a regularized maximum likelihood cost function that fully takes this dependency into account. The scheme is validated by numerical simulations. It is particularly advantageous at low photon numbers and when the premises for deconvolution-based reconstructions are not met. Our reconstruction scheme hence enables a broader applicability of X-ray grating interferometry in imaging and wave front sensing.
CRIS-Team Scopus Importer:2020-05-22

Noise reduction for single-shot grating-based phase-contrast imaging at an x-ray backlighter - Schreiner, Stephan; Akstaller, Bernhard; Dietrich, Lou; Meyer, Pascal; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Zielbauer, Bernhard; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2021)
X-ray backlighters allow the capture of sharp images of fast dynamic processes due to extremely short exposure times. Moiré imaging enables simultaneously measuring the absorption and differential phase-contrast (DPC) of these processes. Acquiring images with one single shot limits the X-ray photon flux, which can result in noisy images. Increasing the photon statistics by repeating the experiment to gain the same image is not possible if the investigated processes are dynamic and chaotic. Furthermore, to reconstruct the DPC and transmission image, an additional measurement captured in absence of the object is required. For these reference measurements, shot-to-shot fluctuations in X-ray spectra and a source position complicate the averaging of several reference images for noise reduction. Here, two approaches of processing multiple reference images in combination with one single object image are evaluated regarding the image quality. We found that with only five reference images, the contrast-to-noise ratio can be improved by approximately 13% in the DPC image. This promises improvements for short-exposure single-shot acquisitions of rapid processes, such as laser-produced plasma shock-waves in high-energy density experiments at backlighter X-ray sources such as the PHELIX high-power laser facility.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Grating-based phase-contrast; Image processing; Image quality improvement; Single-shot X-ray phase-contrast imaging; X-ray back-lighter; X-ray generators and sources

Single-exposure X-ray phase imaging microscopy with a grating interferometer - Wolf, Andreas; Akstaller, Bernhard; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Meyer, Pascal; Schropp, Andreas; Schuster, Max; Seifert, Maria; Weule, Mareike; Michel, Thilo; et al. (Journal of Synchrotron Radiation, 2022)
The advent of hard X-ray free-electron lasers enables nanoscopic X-ray imaging with sub-picosecond temporal resolution. X-ray grating interferometry offers a phase-sensitive full-field imaging technique where the phase retrieval can be carried out from a single exposure alone. Thus, the method is attractive for imaging applications at X-ray free-electron lasers where intrinsic pulse-to-pulse fluctuations pose a major challenge. In this work, the single-exposure phase imaging capabilities of grating interferometry are characterized by an implementation at the I13-1 beamline of Diamond Light Source (Oxfordshire, UK). For comparison purposes, propagation-based phase contrast imaging was also performed at the same instrument. The characterization is carried out in terms of the quantitativeness and the contrast-to-noise ratio of the phase reconstructions as well as via the achievable spatial resolution. By using a statistical image reconstruction scheme, previous limitations of grating interferometry regarding the spatial resolution can be mitigated as well as the experimental applicability of the technique.
CRIS-Team Scopus Importer:2022-05-27
Keywords: grating interferometry; phase contrast X-ray imaging; phase retrieval; X-ray microscopy

Single-shot grating-based phase-contrast imaging of a micrometer sample at a laser-driven x-ray backlighter source - Akstaller, Bernhard; Schreiner, Stephan; Hofmann, Fabian; Meyer, P.; Neumayer, P.; Schuster, Max; Wolf, Andreas; Zielbauer, B.; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Instrumentation, 2021)
A single-shot x-ray phase-contrast imaging technique with short exposure time allows to capture sharp images of fast dynamic processes despite low absorption contrast. We demonstrate the capabilities of a robust single-shot grating-based phase-contrast imaging setup at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. A static test sample was imaged at 47-fold magnification using a laser-driven high-energy x-ray backlighter source. The retrieved transmission and phase-contrast images yield reproducible results. The reconstructed differential phase-images are quantitatively explained. In addition to the phase-images, propagation signatures are found in the data and used for result verification. The obtained results demonstrate the capabilities of the grating setup which can be used to image microscopic dynamic processes in high-energy density plasma experiments at PHELIX or similar high-power laser facilities.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Three-dimensional imaging of xylem at cell wall level through near field nano holotomography - Koddenberg, Tim; Greving, Imke; Hagemann, Johannes; Flenner, Silja; Krause, Andreas; Laipple, Daniel; Klein, Kim C.; Schmitt, Uwe; Schuster, Max; Wolf, Andreas; Seifert, Maria; Ludwig, Veronika; et al. (Scientific Reports, 2021)
Detailed imaging of the three-dimensionally complex architecture of xylary plants is important for studying biological and mechanical functions of woody plants. Apart from common two-dimensional microscopy, X-ray micro-computed tomography has been established as a three-dimensional (3D) imaging method for studying the hydraulic function of wooden plants. However, this X-ray imaging method can barely reach the resolution needed to see the minute structures (e.g. pit membrane). To complement the xylem structure with 3D views at the nanoscale level, X-ray near-field nano-holotomography (NFH) was applied to analyze the wood species Pinus sylvestris and Fagus sylvatica. The demanded small specimens required focused ion beam (FIB) application. The FIB milling, however, influenced the image quality through gallium implantation on the cell-wall surfaces. The measurements indicated that NFH is appropriate for imaging wood at nanometric resolution. With a 26 nm voxel pitch, the structure of the cell-wall surface in Pinus sylvestris could be visualized in genuine detail. In wood of Fagus sylvatica, the structure of a pit pair, including the pit membrane, between two neighboring fibrous cells could be traced tomographically.
CRIS-Team Scopus Importer:2021-03-19

X-ray Dark-Field Imaging for Improved Contrast in Historical Handwritten Literature - Akstaller, Bernhard; Schreiner, Stephan; Dietrich, Lou; Rauch, Constantin; Schuster, Max; Ludwig, Veronika; Hofmann-Randall, Christina; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2022)
If ancient documents are too fragile to be opened, X-ray imaging can be used to recover the content non-destructively. As an extension to conventional attenuation imaging, dark-field imaging provides access to microscopic structural object information, which can be especially advantageous for materials with weak attenuation contrast, such as certain metal-free inks in paper. With cotton paper and different self-made inks based on authentic recipes, we produced test samples for attenuation and dark-field imaging at a metal-jet X-ray source. The resulting images show letters written in metal-free ink that were recovered via grating-based dark-field imaging. Without the need for synchrotron-like beam quality, these results set the ground for a mobile dark-field imaging setup that could be brought to a library for document scanning, avoiding long transport routes for valuable historic documents.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cultural heritage; grating-based phase-contrast imaging; X-ray dark-field imaging